Prestasi Belajar Siswa Dalam Pembelajaran Kooperatif Tipe TAI dan Jigsaw Ditinjau Dari Kecerdasan Majemuk - Nugroho, Arif Ganda; Husni, Muhammad (Media Pendidikan Matematika, 2020)
The purpose of this study was to determine student achievement in the TAI and Jigsaw cooperative learning model in terms of multiple intelligences. This research method is a quasi experiment. The population of this study was students of Class VIII Middle Schools in the city of Banjarmasin, while the sample was VIII Class students of SMPN 1 Banjarmasin, SMPN 7 Banjarmasin and SMPN 14 Banjarmasin. Data analysis was performed inferential statistics. The results of the study indicate that (1) There are significant differences in student achievement in each of the TAI and Jigsaw cooperative learning models before and after treatment; (2) there is no significant difference in student achievement between linguistic intelligence, mathematical logic and others; (3) there is no significant difference in student achievement between linguistic intelligence, mathematical logic and others in the implementation of the TAI type learning model; (4) there is no significant difference in student achievement between linguistic intelligence, mathematical logic and others in the implementation of Jigsaw type learning models; (5) There is a significant difference between students' learning achievement and linguistic intelligence between learning models type TAI and Jigsaw